Vibrational Assignments and Electronic Structure Calculations for Chlorambucil - Gunasekaran, S.; Kumaresan, S.; Arun Balaji, R.; Anand, G. (Asian Journal of Chemistry, 2010)
The Fourier transform Raman and Fourier transform infrared spectral measurements made on chlorambucil and were recorded in the solid phase. The equilibrium geometrical structure and harmonic vibrational spectra have been computed at RHF/6-31G(d,p) and B3LYP/6-31G(d,p) levels. A complete vibrational assignment aided by the theoretical harmonic frequency analysis has been proposed. The B3LYP/6-31G(d,p) geometrical parameters and frequencies of the CH2Cl in the side chains of a cyclohexane are in good agreement with the experi-ment. The observed frequencies are used to compute the thermodynamic functions, namely, the enthalpy and entropy at temperature range 273-400 K and one atmospheric pressure.